2022
DOI: 10.3390/nu14030663
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals: A New Challenge against Cadmium-Induced Testicular Injury

Abstract: Cadmium (Cd) is a widespread heavy metal and a ubiquitous environmental toxicant. For the general population, the principal causes of Cd exposure are cigarette smoking, air pollution and contaminated water and food consumption, whereas occupational exposure usually involves humans working in mines or manufacturing batteries and pigments that utilize Cd. The aim of the present review is to evaluate recent data regarding the mechanisms of Cd-induced testicular structural and functional damages and the state of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 133 publications
0
16
0
Order By: Relevance
“…Many studies showed that the rational intake of typical plant-based eating patterns, such as the Mediterranean-style diet and some antioxidant/anti-inflammatory compounds, including COX/LOX modulators and isoflavones, could be used in the prevention of noncommunicable diseases, including neurodegenerative diseases [ 52 , 53 ]. Due to low toxicity and high pharmacological activity, Pleurotus sajor-caju polysaccharides, in combination with antioxidant compounds, could be added to nutraceuticals, which provides a possible further strategy in the therapy of neuroinflammatory diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies showed that the rational intake of typical plant-based eating patterns, such as the Mediterranean-style diet and some antioxidant/anti-inflammatory compounds, including COX/LOX modulators and isoflavones, could be used in the prevention of noncommunicable diseases, including neurodegenerative diseases [ 52 , 53 ]. Due to low toxicity and high pharmacological activity, Pleurotus sajor-caju polysaccharides, in combination with antioxidant compounds, could be added to nutraceuticals, which provides a possible further strategy in the therapy of neuroinflammatory diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, antioxidants are also recommended for the treatment of infertility to protect testis from endogenous oxidants and it has been reported that consumption of antioxidant supplements by men may increase the live birth rate in infertile couples [ 26 ]. Nutraceuticals are being increasingly recommended to prevent testicular injury due to toxicants [ 27 ]. B. sacra is a well-known antioxidant and it is known to protect several organs against oxidative damage both in vivo and in vitro [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] As there is no particular medication for the prevention or treatment of the morbidity and mortality associated with Cd exposure, new therapeutic agents are required. 14,[17][18][19] Qiangjing tablets (QJPs) were developed by the Affiliated Hospital of Chengdu University of Traditional Chinese Medicine, are composed of a number of traditional Chinese herbs that help increase testicular function and sperm motility. [17][18][19] We have used QJP in male infertility treatment for over 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…14,[17][18][19] Qiangjing tablets (QJPs) were developed by the Affiliated Hospital of Chengdu University of Traditional Chinese Medicine, are composed of a number of traditional Chinese herbs that help increase testicular function and sperm motility. [17][18][19] We have used QJP in male infertility treatment for over 20 years. QJP may improve the quality of sperm in asthenospermic rats by inhibiting apoptosis and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation